In situ MEMS testing: correlation of high-resolution X-ray diffraction with mechanical experiments and finite element analysis. Issue 1 (1st January 2017) - Schifferle, Andreas; Dommann, Alex; Neels, Antonia
Abstract: New methods are needed in microsystems technology for evaluating microelectromechanical systems (MEMS) because of their reduced size. The assessment and characterization of mechanical and structural relations of MEMS are essential to assure the long-term functioning of devices, and have a significant impact on design and fabrication. Within this study a concept for the investigation of mechanically loaded MEMS materials on an atomic level is introduced, combining high-resolution X-ray diffraction (HRXRD) measurements with finite element analysis (FEA) and mechanical testing. In situ HRXRD measurements were performed on tensile loaded single crystal silicon (SCSi) specimens by means of profile scans and reciprocal space mapping (RSM) on symmetrical (004) and (440) reflections. A comprehensive evaluation of the rather complex XRD patterns and features was enabled by the correlation of measured with simulated, 'theoretical' patterns. Latter were calculated by a specifically developed, simple and fast approach on the basis of continuum mechanical relations. Qualitative and quantitative analysis confirmed the admissibility and accuracy of the presented method. In this context [001] Poisson's ratio was determined providing an error of less than 1.5% with respect to analytical prediction. Consequently, the introduced procedure contributes to further going investigations of weak scattering being related to strain and defects in crystalline structures and therefore supports investigations on materials and devices failure mechanisms. Abstract :